Effect of Cadmium Chloride on the Histoarchitecture of Certain Organs of a Freshwater Catfish, Clarias batrachus - Dar, B.A.; Qureshi, T.A.; Khaliq, R. (Our Nature, 2012)
The present study was conducted to investigate the effects of cadmium chloride induced histological alterations in the liver and kidney of a freshwater catfish, Clarias batrachus. The fishes were exposed to 4 ppm (4% of 96 h LC50) and 8 ppm (8% of 96 h LC50) of cadmium chloride for 60 days. The most common changes in liver at all doses of cadmium chloride were loosening of hepatic tissue, vacuolated cell cytoplasm, enucleation and eccentric nuclei. In the kidney of fish exposed cadmium chloride were characterized by loosening of haemopoietic tissue, uriniferous tubules have lost their original appearance, vacuolated cytoplasm, degeneration in the epithelial cells of renal tubule, narrowing of the tubular lumen and damaged glomeruli. DOI: http://dx.doi.org/10.3126/on.v9i1.5737